The double-digit club - Bauer, Marion Dane. (New York : Scholastic Inc, 2004)
Nine-year-old Sarah is excited about summer vacation, but she faces unexpected crises when her best friend Paige becomes old enough to join a local girls' clique, and when she makes choices which affect her relationship with an elderly blind neighbor.
Keywords: Best friends -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Clubs -- Fiction; Blind -- Fiction; People with disabilities -- Fiction